Pelatihan Kebersyukuran Untuk Meningkatkan Kesejahteraan Subjektif Remaja di Masa Pandemi Covid-19 - Dianing Ratri Saraswati; Taufiq, Tsoraya Dina; Desiana Risqi Hana; Lestari, Sri (Ilin Institute, 2021)
This community service aims to improve subjective well-being and reduce stress for high school students who are taking online learning during the Covid-19 pandemic through gratitude training. Seven high school teenagers were involved in this activity. The method used in this community service is an experiment by giving a pre-test and post-test in the form of a subjective well-being scale and a stress scale, as well as being given gratitude training. The results showed that the trainees were able to apply gratitude in their daily lives so that they experienced an increase in subjective well-being and a decrease in stress. Teenagers feel the benefits of this gratitude training and plan to continue to apply it in their daily lives..